A Tomada de decisão na previdência social: uma reflexão sobre as ações do produtor de informações da DATAPREV - Velho, Ana Cristina Meirelles (2008)
The research investigated the information analysis process performed by Dataprev to support decision making in Brazilian Social Security in order to improve this service. It considered the assumption that the control of information is one of the possible ways to decision making in the context of public policies. The theoretical support linked the ideas from Information Science, Political Science, Computer Science and Management. Methods of qualitative nature have been used: document and bibliographical analysis and interviews. The model proposed by Kielgast and Hubbard, based on Taylor´s ideas, is used to examine the steps of the chosen case study: a campaign to disseminate information for taxi and motorcycles drivers, promoted by the Social Security Education Program. The results obtained indicate the points that could be reviewed in Dataprev´s process to improve its generation of information products, as well as suggest complementary studies which could be developped in the future to contribute with the subject of this research.